Systems approach to design multi-epitopic peptide vaccine candidate against fowl adenovirus structural proteins for Gallus gallus domesticus - Mugunthan, Susithra Priyadarhni; Venkatesan, Divyadharshini; Govindasamy, Chandramohan; Selvaraj, Dhivya; Harish, Mani Chandra (Frontiers in Cellular and Infection Microbiology, 2024)
Fowl adenovirus (FAdV), a non-enveloped virus with icosahedral symmetry and a size ranging from 70-90 nm, belongs to the Aviadenovirus genus within the Adenoviridae family. It is associated with various chicken diseases, including hepatitis-hydropericardium, inclusion body hepatitis, and gizzard erosion. Specific FAdV serotypes are linked to distinct conditions: FAdV-4 to hepatitishydropericardium syndrome, FAdV-2, -8a, -8b, and -11 to inclusion body hepatitis, and FAdV-1 to gizzard erosion. The increasing global prevalence of FAdV-related diseases necessitates proactive prevention measures, such as robust vaccination strategies and heightened biosecurity protocols.Utilizing the potential of viral structural proteins, we employed an in silico approach to design a multi-epitope vaccine. This innovative vaccine targets essential viral structural proteins-hexon, penton, and fiber protein-to predict T-cell and B-cell epitopes binding to MHC-I and MHC-II molecules. Our methodology was validated through molecular docking studies, assessing the interaction of the multi-epitope vaccine candidate with chicken Toll-like receptors 2 and 5. These findings underscore the structural integrity of the designed multi-epitope vaccine and its promising ability, through the in silico approach, to induce a robust immunological response against FAdV infections in chickens.